2020
DOI: 10.1097/wno.0000000000000872
|View full text |Cite|
|
Sign up to set email alerts
|

Idiopathic Intracranial Hypertension and Anemia: A Matched Case–Control Study

Abstract: Background: An association between idiopathic intracranial hypertension (IIH) and anemia has been speculated from previous case reports and case series. Retrospective studies to date have not used matched case controls to compare standardized complete blood count (CBC) values for the presence of anemia. Methods: At our tertiary care facility, 50 patients with IIH were matched with 50 case–control patients to compare CBC values from laboratory affiliates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 28 publications
1
20
1
Order By: Relevance
“…Table 2 summarizes the studies that investigated prevalence of anemia among patients with IIH (4,11,(20)(21)(22)(23). The weighted incidence of anemia in patients with IIH among 7 studies was 195/1,073 (18.2%).…”
Section: Results Of Larger Prevalence Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 2 summarizes the studies that investigated prevalence of anemia among patients with IIH (4,11,(20)(21)(22)(23). The weighted incidence of anemia in patients with IIH among 7 studies was 195/1,073 (18.2%).…”
Section: Results Of Larger Prevalence Studiesmentioning
confidence: 99%
“…However, the relationship between anemia and IIH remains controversial as iron deficiency anemia is also common in young women of childbearing age. In addition, larger controlled studies have failed to reveal an association between anemia and IIH despite numerous case reports supporting their causal relationship (4,11).…”
mentioning
confidence: 99%
“…In a retrospective study from China, anemia with IIH (22/153) was associated with shorter disease duration and better visual outcome following correction of anemia [13]. In another case-control study, no significant difference was observed between anemic patients with IIH and matched controls with other ophthalmic diagnoses [14]. Our patient also required additional treatment with carbonic anhydrase inhibitors, steroids, and serial lumbar punctures as the symptoms did not alleviate with the initial blood transfusion.…”
Section: Discussionmentioning
confidence: 66%
“…Although IIH most commonly affects anemic menstruating women, the causation between anemia and raised ICP could not be explained by a retrospective, matched case-control study conducted by Lin et al In their study, no statistically significant association was found between the complete blood count values in patients diagnosed with IIH compared with the controls [ 14 ]. However, there is substantial evidence in literature where symptomatic resolution of papilledema was seen with the prompt correction of anemias [ 4 ].…”
Section: Discussionmentioning
confidence: 99%